2012
DOI: 10.1584/jpestics.d11-024
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methyl parathion by surfactant-assisted soil washing and subsequent wastewater biological treatment

Abstract: e aim of this work is to present an integrated process for the remediation of soils contaminated with o,o-dimethyl o-(pnitrophenyl)phosphorothioate, known as methyl parathion (MP), by surfactant-enhanced soil washing and treatment of the produced wastewaters in an aerobic-submerged bio lter. Soils containing approximately 0.4 and 13 mg/kg of MP were washed using anionic, nonionic, zwitterionic, and natural surfactants. Between 63 and 98% of the initial concentrations of MP were removed. Wastewater produced fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The results showed that, using the 1% (w/w) TX-100 washing solution, more than 84% of pentachlorophenol could be extracted from fine sandy soil and silt [94]. In Torres's research, 88% of methyl parathion in soil was removed under the same TX-100 concentration [95]. Rios et al [96] inspected the efficiencies of two kinds of nonionic surfactants on the desorption of dichloro diphenyl trichloroethane (DDT) from soils.…”
Section: Nonionic Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that, using the 1% (w/w) TX-100 washing solution, more than 84% of pentachlorophenol could be extracted from fine sandy soil and silt [94]. In Torres's research, 88% of methyl parathion in soil was removed under the same TX-100 concentration [95]. Rios et al [96] inspected the efficiencies of two kinds of nonionic surfactants on the desorption of dichloro diphenyl trichloroethane (DDT) from soils.…”
Section: Nonionic Surfactantsmentioning
confidence: 99%
“…Bordas [131] conducted a series of dynamic column elution tests, suggesting that rhamnolipids at a high concentration (5.0 g/L) could remove ~70% of the pyrene in soil. At a low dose of 0.1 wt%, locust bean gums washing liquid was able to extract 99.5~99.7% of methyl parathion from contaminated soil, and the removal efficiency obtained by gums was 84.2~99.7% [95]. Jorfi et al [132] used the biosurfactant extracted from Pseudomonas aeruginosa SP4 to enhance pyrene removal from the contaminated soil.…”
Section: Extraction Of Has From Natural Soils Is Laborious With Low Ymentioning
confidence: 99%
“…Surfactants are also used to increase the bioavailability of pesticides to be degraded by soil microorganisms. In the paper from Torres et al (2012) the removal of methyl parathion using anionic, non-ionic, cationic and natural surfactants was studied, and wastewater was biologically treated.…”
Section: Solventsmentioning
confidence: 99%
“…In Mexico, MP is one of the most commonly used pesticides and has been used extensively for insect control with crops, including avocados, rice, onions, peaches, spinach, and strawberries. Although the use of MP is legal, its trade has recently been restricted (Torres, Ramos, Avila, & Ortiz, ), and it can be found in soil and water, as well as in waste. It is considered extremely dangerous and is included in the Ia Category of the World Health Organization (WHO, ).…”
Section: Introductionmentioning
confidence: 99%